Costs by ASTM A36 iron corrosion in hydrometalurgic auriferous processes. Comparison between cyanide and thiourea - Romero Bonilla, Hugo Ítalo (2017)
The objective of this research was to determine corrosion rate (Vcorr) iron ASTM A36, in solutions of sodiumx cyanide and thiourea. Further evaluate the effect of this electrochemical phenomenon in costs associated with gold leaching processes. The corrosion rate was determined in mm / year by polarization curves. Costs were determined by a cost analysis using synthetic indicators. The corrosion rate of iron ASTM A36 in sodium cyanide solutions in concentrations of 0.62 g / L; 0.80 g / L and thiourea solutions 0.96 g / L; 1.24 g / L was evaluated. The results show that the corrosion rate of the metal is slightly higher in the solution of thiourea 1.24 g / L (3.03 mm / year) with the following behavior: Thiourea 1.24g / L> Thiourea 0.96 g / L> Cyanide 0.80 g / L ≈ Cyanide 0.62 g / L. It was estimated that corrosion costs in gold leaching processes are between 4.78 and 5.20% of the capital for cyanide and thiourea respectively.